God met ons! Die aanspraak op Goddelike steun in "n konfliksituasie volgens die Ou Testament - Balzer, H. R. (Hervormde teologiese studies, 1991)
God with us! The claim of divine support in a situation of conflict, seen from an Old Testament perspective Political discussions referring to Old Testament texts in order to claim divine support for one’s views, and disqualify opposing opinions as being in conflict with the God of the Bible, are hermeneutically based on analogies between a revealed God, His representatives or laws, and ethical or political principles. A synchronic investigation of relevant Old Testament passages fully denies and opposes this hermeneutic approach, which is based on an isolation of principles or norms - with no reg ard to the only relevant actual relation to God himself. Any political identification with God or associated function must therefore be rejected as blasphemous from an Old Tes-tament perspective.